Materials Design on the Origin of Gap States in a High-κ/GaAs Interface. (September 2015) - Wang, Weichao; Gong, Cheng; Xiong, Ka; Santosh, K.C.; Wallace, Robert M.; Cho, Kyeongjae
ABSTRACT: Given the demand for constantly scaling microelectronic devices to ever smaller dimensions, a SiO2 gate dielectric was substituted with a higher dielectric-constant material, Hf(Zr)O2, in order to minimize current leakage through dielectric thin film. However, upon interfacing with high dielectric constant (high-κ) dielectrics, the electron mobility in the conventional Si channel degrades due to Coulomb scattering, surface-roughness scattering, remote-phonon scattering, and dielectric-charge trapping. III-V and Ge are two promising candidates with superior mobility over Si. Nevertheless, Hf(Zr)O2 /III-V(Ge) has much more complicated interface bonding than Si-based interfaces. Successful fabrication of a high-quality device critically depends on understanding and engineering the bonding configurations at Hf(Zr)O2 /III-V(Ge) interfaces for the optimal design of device interfaces. Thus, an accurate atomic insight into the interface bonding and mechanism of interface gap states formation becomes essential. Here, we utilize first-principle calculations to investigate the interface between HfO2 and GaAs. Our study shows that As−As dimer bonding, Ga partial oxidation (between 3+ and 1+) and Ga− dangling bonds constitute the major contributions to gap states. These findings provide insightful guidance for optimum interface passivation.